A Study Of The Relevance Of Sustainable Development: A Historical Perspective (International Journal of Food and Nutritional Sciences, 2022)
The important and much talked about phrase sustainable development is a notion that requires societies to lead a harmonious life in interaction with others in countryside and support everybody’s existential needs accepting that the perpetual future generations shall also support their survival needs on their own. It is a pro nature way for people on earth to use natural resources deprived of letting these resources run out of stock. This essentially means planning and enabling systemic development without allowing damage, deterioration.